(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
The geomorphometric characteristics of the Hasab catchment in the Iraqi southern desert are studied. The study utilized geospatial data, including the Digital Elevation Model (DEM) (SRTM), satellite imagery, and topographic maps, to analyze the geomorphometric characteristics of a watershed and then incorporated them into a topological model. The order priorities were ranked from 2677 to 167, with percentages of 35.316%, 23.245%, 16.596%, 11.728%, 10.910%, and 2.2031. The Hasab watershed has 4342.563 km of stream length, with Hasab sub-watershed (1) accounting for 50.882% and Hasab sub-watershed (4) 28.045% having the second-most length. The bifurcation ratios of sub-watersheds vary based on geological and climatic data, with the highest ratio in the Hasab sub-watershed at 10.235, followed by others at 2.151, 2.318, and 1.263. The Hasab watershed’s stream frequency is 1.421 km/km2, with sub-watershed rates increasing to 2.126 km/km2. Sub-watershed values range from 2.958 km/km2 to 1.252 km/km2. The Hasab watershed has a drainage density of 1.387 km/km2, with sub-watersheds having varying density values. The highest density is 1.392 km/km2 in Hasab sub-watershed (4), while the lowest is 0.716 km/km2 in Hasab sub-watershed (3). The Hasab watershed has a basin texture rate of 11.290 Stream/km, with the highest value in Hasab sub-watershed (4) and the lowest in Hasab sub-watershed (2). Factors like basin area, rock formation hardness, structural features, rainfall intensity, slopes, basin shape, and vegetation density influence stream order diversity in basins. Waterway length rates and bifurcation ratios vary, with first-order streams transitioning into second-order ones due to river captivity.